Diagnostic Validity of Flagellin Gene (fliC) in Urine for the Detection of Typhoid Fever (Bangladesh Journal of Medical Microbiology, 2023)
Background: Accurate diagnosis of typhoid fever is important issue for the treatment of the patients. Objective: The purpose of the present study was to evaluate the nested PCR for the diagnosis of suspected cases of typhoid fever targeting the flagellin gene (fliC) of Salmonella Typhi from urine. Methodology: This cross sectional study was conducted in the Department of Microbiology of Dhaka Medical College (DMC), Dhaka. Specimens were collected from OPD of DMCH, Dhaka Shishu Hospital (DSH), Dhaka and National Institute of Neurosciences and Hospital (NINSH), Dhaka from July 2013 to June 2014 for a period of one year. All suspected patients of typhoid fever irrespective of age, sex and history of antibiotic intake who attended the OPD of DMCH, DSH and NINSH were selected for this study. Diagnosed cases of febrile illness other than typhoid fever were excluded from the study. Blood and urine were collected and all isolates were tested for antimicrobial susceptibility by Kirby-Bauer modified disc-diffusion technique. Widal test and CRP were performed. Nested PCR was performed in the urine and blood to detect the DNA of Salmonella Typhi. Results: Among 72 typhoid fever patients, 33(45.8%) were Widal test positive and 42(55.5%) were blood culture positive. Out of 30 blood culture negative patients nested PCR in urine was positive in 5(16.7%) cases. The sensitivity, specificity, PPV, NPV and accuracy of nested PCR in urine were 97.6%, 83.3%, 89.1%, 96.1% and 91.7% respectively.Conclusion: In conclusion the nested PCR for the diagnosis of typhoid fever targeting the flagellin gene (fliC) of Salmonella Typhi from urine may be very useful diagnostic tool.Bangladesh Journal of Medical Microbiology, January 2023;17(1):34-39